(untitled) (Journal of Comparative & International Higher Education, 2024)
This study explores the impact of individual dimensions in Internationalisation of Higher Education (IHE) on educational developers in a Collaborative Online International Learning (COIL) teacher training program. Focusing on 10 educational developers, the study utilizes narrative interviews to delve into their personal and professional growth. Through storytelling, transformative processes emerge, revealing shifts in perspectives, pedagogical approaches, cultural humility, and professional practices. Using a narrative inquiry approach, the study highlights facets such as cultural humility, global citizenship, and a sense of belonging. Inductive thematic interpretation underscores the course’s role as a crucible for understanding internationalisation dynamics. The research contributes valuable insights into educational developers’ growth, positioning them as pivotal in the global transformation of higher education.